Modelos alométricos en la relación diámetro - altura total en plantas de Swietenia macrophylla King con dosis de fertilización foliar. Puerto Almendra, Loreto, Perú-2021 - Ruiz Capuena, Leydy Conny (2025)
The present study aimed to establish the diameter–total height relationship in Swietenia macrophylla King (“mahogany”) under the application of three foliar fertilization doses with Bayfolan, through the fitting of eleven allometric models. The research was conducted at the Forest Research and Teaching Center (CIEFOR) of the Faculty of Forestry Sciences of UNAP, following an analytical design, explanatory level, and quantitative–correlational approach. Three treatments were evaluated: Dose 1 (1 0/00), Dose 2 (2 0/00), and Dose 3 (3 0/00). Results showed that for Dose 1 (1 0/00), the S-curve model presented the best fit (r = 0.880; R² = 77.4%), demonstrating an excellent relationship between diameter and height, with the prediction equation Y = 2.71828*6.003(-23.514/t). For Dose 2 (2 0/00), the cubic model was the most representative (r = 0.787; R² = 61.9%), indicating a strong relationship between the study variables, with the prediction equation Y = 137.9 + (-6.498 x t) + (0.327 x t²) + (- 0.001 x t³). Meanwhile, for Dose 3 (3 0/00), the linear, quadratic, and cubic models reached similar fits (r = 0.825; R² = 68%), showing a strong association between the study variables, with the prediction equations: linear Y = -12.483 + (7.620 x t), quadratic Y = 11.752 + (5.117 x t) + (0.060 x t²), and cubic Y = 11.752 + (5.117 x t) + (0.060 x t²)+ (0.000 x t³). Therefore, foliar fertilization influences the diameter–height relationship of Swietenia macrophylla King, allowing the identification of reliable allometric models to estimate height and diameter growth more precisely. These findings will contribute to optimizing plantation management and strengthening sustainable reforestation strategies in the Amazon.